Response Surface Methodology for Optimizing the Production of Biosurfactant by Candida tropicalis on Industrial Waste Substrates - Almeida, Darne G.; Soares da Silva, Rita de Cássia F.; Luna, Juliana M.; Rufino, Raquel D.; Santos, Valdemir A.; Sarubbo, Leonie A. (Frontiers in Microbiology, 2017)
Biosurfactant production optimization by Candida tropicalis UCP0996 was studied combining central composite rotational design (CCRD) and response surface methodology (RSM). The factors selected for optimization of the culture conditions were sugarcane molasses, corn steep liquor, waste frying oil concentrations and inoculum size. The response variables were surface tension and biosurfactant yield. All factors studied were important within the ranges investigated. The two empirical forecast models developed through RSM were found to be adequate for describing biosurfactant production with regard to surface tension (R2 = 0.99833) and biosurfactant yield (R2 = 0.98927) and a very strong, negative, linear correlation was found between the two response variables studied (r = - 0.95). The maximum reduction in surface tension and the highest biosurfactant yield were 29.98 mNm-1 and 4.19 gL-1, respectively, which were simultaneously obtained under the optimum conditions of 2.5 % waste frying oil, 2.5 %, corn steep liquor, 2.5 % molasses and 2 % inoculum size. To validate the efficiency of the statistically optimized variables, biosurfactant production was also carried out in 2 and 50L bioreactors, with yields of 5.87 gL-1 and 7.36 gL-1, respectively. Finally, the biosurfactant was applied in motor oil dispersion, reaching up to 75% dispersion. Results demonstrated that the CCRD was suitable for identifying the optimum production conditions and that the new biosurfactant is a promising dispersant for application in the oil industry.